Swedish teenagers’ difficulties and abilities to determine digital news credibility - Nygren Thomas; Guath Mona (Nordicom Review, 2019)
In this study we investigate the abilities to determine the credibility of digital news among 483 teenagers. Using an online survey with a performance test we assess to what extent teenagers are able to determine the credibility of different sources, evaluate credible and biased uses of evidence, and corroborate information. Many respondents fail to identify the credibility of false, biased and vetted news. Respondents who value the importance of credible news seem to hold a mindset helping them to determine credibility better than other respondents. In contrast, respondents self-reporting to be good at searching information online and who find information online trustworthy are not very good at civic online reasoning. Our findings, which may be linked to theories of disciplinary literacy, science curiosity and overconfidence, provide a basis for further research of how to better understand and support civic online reasoning in classrooms and society.